PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAPSTRES KERJA PADA PERUSAHAAN FREIGHT FORWARDING DI SURABAYA - Tabriza Thirafia; Irma Rustini Aju; Devina Puspita Sari (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Freight forwarding was a company that, for a fee, organized shipments for the shipper by liaising with carriers. To achieve corporate objectives, human resources management was needed. Some work errors, such as being less careful in entering data, resulted in cost losses, and there were some tasks that remained unfinished after exceeding the deadline due to work stress. The work stress was affected by the work environment and workload. This study aimed to analyze the impact of the work environment and workload on work stress in employees. Using saturated sampling, the sample for this research consisted of 27 employees in one of freight forwarding company in Surabaya. Data was analyzed by multiple linear regression analysis as its method and using software SPSS 22. The results showed that the value of the work environment in the mentioned company was 0.00, where the value < 0.05. It implied that the work environment had a positive significant impact on work stress. Concurrently, the value of the workload there was 0.315, where the value > 0.05 and implied that the workload had no impact on work stress. Based on the F test, the value showed 0.001 < 0.05 and implied that the work environment and workload simultaneously had an impact on work stress.